THE AIR QUALITY MONITORING IN DEVELOPMENT LOCATION TANJUNG JATI STEAM POWER PLANTS 5&6 - INDONESIA - Isworo, Slamet; Oetari, Poerna Sri; Adji, Tosan (International Journal of Psychosocial Rehabilitation, 2020)
Background and Objectives: Development of Tanjung Jati steam power plant unit 5-6 was developed to meet the electricity needs especially in Java and Bali. In its development necessary to monitor the impacts that might occur due to the decrease in air quality aimed at controlling and monitoring air quality during the construction of the steam power plant. Material and Method: The study was conducted experimentally on the parameters of Total Suspended Particulate, Carbon Monoxide, NO2, SOx, Air Temperature, Humidity, Wind Speed, PM 2.5 and PM 10 , which then compared descriptively with water quality standards based on Central Java Governor decree No. 8 of 2001. The trend evaluation modeling of air quality modeling used a trend line regression. Result: Based on the analysis results for all air quality parameters were still below the quality standard, then a trend model was made for each parameter PM 10 and PM 2.5 model trends are y = (2.9267) x + 77.086 and y = (0.022) x + 36.509, temperature and humidity model trends y = 0.587 x + 62.531 and y = (0.1533) x + 30.955. The SOX trend model is y = 6.0715 x 5.3799. The conclusion was that all parameters are below the quality standard, however, the humidity and SO2 parameters have a positive trend model that was likely to had an impact on the future, therefore it needs attention in its management.